The impact of environmental taxes on economic benefits and technology innovation input of heavily polluting industries in China - Wang, Zhengyan; Zhu, Naiping; Wang, Jianuo; Hu, Yingyun; Nkana, Mwansa (Frontiers in Environmental Science, 2022)
This paper sets the heavily polluting enterprises as the treatment group based on the relevant data of listed companies in the five years from 2016 to 2020, and the companies other than the heavily polluting enterprises as the control group. It performs an empirical analysis on the impact of China's environmental tax on the economic performance and technological innovation of industries that pollute heavily through the double-difference technique. The findings show that since the inception of environmental tax in China, the positive effect of environmental tax on the economic performance and technological innovation of heavily polluting industries is more substantial. Eventually, as a result of the fact that some enterprises in heavy pollution industries are under increased financial pressure because of green upgrades and the environmental tax rate in some regions is too low, two recommendations are presented to enhance the green upgrade subsidies for enterprises and roughly increase the environmental tax rate.